2021
DOI: 10.3390/ijms22094862
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Dormancy: Implications for Invasion and Metastasis

Abstract: Tumor dormancy refers to a critical stage of cancer development when tumor cells are present, but cancer does not progress. It includes both the concept of cellular dormancy, indicating the reversible switch of a cancer cell to a quiescent state, and that of tumor mass dormancy, indicating the presence of neoplastic masses that have reached cell population equilibrium via balanced growth/apoptosis rates. Tumor dormancy provides the conceptual framework, potentially explaining a major challenge in clinical onco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 123 publications
0
19
0
Order By: Relevance
“…Tumour cell dormancy is an intricate mechanism involving different molecular pathways and cell-cell interactions in accordance with the type of cancer and the microenvironmental signalling [ 32 ]. In our previous work we demonstrated that dormant BrCa cells interact with a specific osteoblast subpopulation, known as spindle-shaped N-Cadherin High osteoblasts (SNOs), remaining cell cycle arrested due to the Notch2 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Tumour cell dormancy is an intricate mechanism involving different molecular pathways and cell-cell interactions in accordance with the type of cancer and the microenvironmental signalling [ 32 ]. In our previous work we demonstrated that dormant BrCa cells interact with a specific osteoblast subpopulation, known as spindle-shaped N-Cadherin High osteoblasts (SNOs), remaining cell cycle arrested due to the Notch2 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that pathological prion isoforms can remain dormant for an extended period of time may be another significant consideration in targeting dormancy in cancer. Cancer cells become dormant when they switch from an active to a quiescent state and cancer dormancy remains a major challenge in clinical oncology where tumor recurrence can resurface years after initial diagnosis [ 664 ]. Not surprisingly, stress has been identified as one of the triggers that can awaken cancer cells from dormancy [ 47 , 665 ], and hypoxic stress that reduces pH is able to activate prion aggregation [ 666 ] and phase separation ( Section 2.3.3 ).…”
Section: Melatonin May Promote Prp Physiological Functions and Inhibi...mentioning
confidence: 99%
“…Solitary disseminated primary tumor cells, once settled in the bone niche, may grow immediately or adopt a nonproliferating dormant state remaining quiescent in the bone marrow for up to decades (“cellular dormancy”) [ 78 , 86 , 87 ]. A comprehensive mechanistic insight into tumor dormancy, including its implications in tumor invasion and metastasis, has recently been provided [ 88 ]. For bone metastases, the fate of colonizing tumor cells most likely depends on their specific location in the bone microenvironment, where around 20% of the endosteal surface undergoes active remodeling, whereas the other 80% remains relatively quiescent at any given time [ 13 ].…”
Section: Mechanisms Of Metastasismentioning
confidence: 99%